Remote Learning and Teaching in Southern Africa: A Case Study of Health Professions Education Institutions - Chipamaunga, Shalote; Nestai Nyoni, Champion; Nantamu Kagawa, Mike; Wessels, Quenton; Kafumukache, Elliot; Gwini, Rudo; Kandawasvika, Gwendoline; Katowa-Mukwato, Patricia; Masanganise, Rangarirai; Nyamakura, Rudo; Nyawata, Idah; Pretorius, Louise; et al. (Research Square, 2021)
Southern Africa, like other parts of the world, has always strived to deliver quality health professions education. These efforts have been influenced to a larger extent by the socio-economic and cultural context of the region, but also by what happens globally. The global disruption caused by the COVID-19 pandemic necessitated the implementation of emergency remote teaching (ERT) to continue delivering on the mandate of educating future health professionals in 2020. The purpose of this research was to describe the change process through which selected health professions education institutions (HPEIs) in the Southern African region adjusted their academic programmes for remote learning and teaching during the COVID-19 related pandemic. Methods A mixed methods study with a case study design was applied using the ADKAR model as a conceptual framework for data interpretation. The study population consisted of educators, students, and administrators in undergraduate medical and nursing programmes from six institutions in five countries. Results A total of 1,307 respondents provided data for the study. Many of the institutions were caught off-guard when most educators and almost all students were required to leave their universities and go into isolation at home. Stakeholders immediately became aware of the need to adopt online approaches as an emergency measure. In all programmes, educators, students, and administrators agreed that they should change and wanted to change, and some students realised that they had to take charge of their own learning independently. Overall educators reported confidence with the use of standard Microsoft software, while knowledge of learning management systems proved more challenging for both educators and students. Many stakeholders, especially students and administrators, reported uncertainty about their ability to function in the new reality. Conducive family dynamics, a quiet space to study, good connectivity, a reliable electricity supply and appropriate devices were reported to reinforce learning and teaching. Conclusions The findings highlight the need to scale up educational infrastructure, prioritise strategic directives, drive continuous professional development of educators and foster co-constructivist approaches towards student centered education, including formal online learning.
Keywords: ADKAR framework; COVID-19; Health professions education; Remote learning and teaching; Southern Africa; Undergraduate programme